Determinan Financial Distress Pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia: Institut Pertanian Bogor - Saraswati, Raras Aisyah; Ratnawati, Anny; Irawan, Tony; Tony (Jurnal Ekonomi dan Kebijakan Pembangunan, 2024)
The purpose of this study is to analyze financial performance of property and real estate companies before and during the Covid-19 pandemic. Next is to analyze financial distress by using the Zmijewski calculation methods and to analyze the factors of financial distress. The populations in this study are property and real estate companies listed on the IDX in year 2018 to 2022. Based on purposive sampling methods, samples obtained are 15 companies in 5 years, so obtained 300 observations. The descriptive methods are used to analyze financial performance, and to analyze Zmijewski’s financial distress using the panel data regression. The result of descriptive analysis show that before the pandemic there were 15 companies in a healthy condition but during the pandemic there was one company experiencing financial distress namely MDLN, and based on the direction of financial distress trends, there are three groups of companies that tend to worsen, improve, and stagnate. The results of data panel regression showed that profitability ratio (ROE), liquidity ratio (CR), and leverage ratio (DER) have a significant value to predict financial distress, whilst activity ratio (TATO), sales growth, interest rate (IR) and exchange rate (ER) which not significant. The trend of financial distress (that are worsening, improving and stagnant), can be used by companies or investors as an early warning system in predicting financial distress in property and real estate companies.